The immersive Show: Experiences of Mediterranean Theatre (Itinera, 2017)
We cannot speak of Gibellina without addressing the idea of time, of memory and of their effects on the present and the future, of its relation to man confronted with ruins. More precisely, with the ruins left by the earthquake that struck the towns that had for centuries stood in the Belice Valley during the night between January 14 and 15, 1968. Since that time, to get back on its feet, Gibellina has engaged in an intensive process of reconstruction, with art and theater as leading players. The Gibellina theater experience is an example of total theater: only a spectator, an active and participating visitor can fully comprehend the scope of a show in which the person is drawn in by a natural event, which serves as prologue and epilogue of each performance.